The Effect of Chewing Gum on Stress in Women with Unexplained Infertility - Ahmet Basar Tekin; Nezihe Kızılkaya Beji; Vehbi Yavuz Tokgöz; Yeliz Kaya; Tuğba Tahta; Tuğba Kartal (Sağlık Bilimleri Üniversitesi Hemşirelik Dergisi)
Introduction: Infertile women may have difficulty coping with the stress caused by assisted reproductive methods.Aim: It was aimed to investigate the effect of chewing gum on stress levels in women with unexplained infertility.Method: Sixty - one women receiving in - vitro fertilization treatment in the tertiary care center were included in the study. A randomized controlled experimental design was established in the study. The group chewing gum for five minutes at least two times a day was called "Experimental Group - 1", the group chewing gum for 20 minutes at least two times a day was called "Experimental Group - 2", and the group not chewing gum was called "Control Group". Reproductive information and stress level data of infertile women were collected with the Descriptive Information Form and Fertility Problem Inventory.Results: No statistically significant difference was found in comparing Fertility Problem Inventory total scores between the groups (p gt; 0.005). However, a statistically signifiant difference was found between the mean values of the denial of life without children, which was a subscale of the Fertility Problem Inventory score according to time in the Experimental Group - 2 group (p lt;0.005).Conclusion: We believe that the positive effect of chewing gum on coping with stress may be an alternative intervention that may contribute positively to coping with the infertility treatment process and should be supported by other interventions.